2021
DOI: 10.1249/jsr.0000000000000798
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Palsy: Sport and Exercise Considerations

Abstract: Cerebral palsy (CP) is a group of debilitating motor disorders that carries a wide array of clinical presentations ranging from isolated physical or cognitive impairment to global loss of function. Despite the prevalence of CP, recommendations and benefits of physical activity/exercise have historically not been clearly defined. The research on the subject has several limitations, including small sample size, power, standardized measures/outcomes, and poor classification regarding severity of the disease. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the absence of research evidence, some clinicians and researchers have vastly underestimated the physical capabilities of this group. One recent review stated that people at GMFCS IV and V ‘…will struggle performing structured exercise programmes’ and ‘are unable to perform activities greater than 1.0 MET’ 30. Note that 1.0 METs is the energy expended during quiet sitting 31.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of research evidence, some clinicians and researchers have vastly underestimated the physical capabilities of this group. One recent review stated that people at GMFCS IV and V ‘…will struggle performing structured exercise programmes’ and ‘are unable to perform activities greater than 1.0 MET’ 30. Note that 1.0 METs is the energy expended during quiet sitting 31.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study raised concerns about the frequency of injections, showing no complete recovery at 6 months [ 25 ], and suggested that longer intervals between reinjections are preferable. The possibility of counteracting atrophy with available drugs or accelerating recovery through the use of other treatments such as exercise or increased physiotherapy might fasten recovery after BoNT treatment [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations. The American College of Sports Medicine provides the following recommendations for people living with cerebral palsy [17]. 1.…”
Section: Things To Consider Before Starting To Exercisementioning
confidence: 99%